2005
DOI: 10.1128/jvi.79.6.3350-3357.2005
|View full text |Cite
|
Sign up to set email alerts
|

Differential Role for TLR3 in Respiratory Syncytial Virus-Induced Chemokine Expression

Abstract: Respiratory syncytial virus (RSV) is the leading cause of lower respiratory tract infection in young infantsworldwide. Previous studies have reported that the induction of interleukin-8/CXCL8 and RANTES/CCL5 correlates with disease severity in humans. The production of these chemokines is elicited by viral replication and is NF-B dependent. RSV, a negative-sense single-stranded RNA virus, requires full-length positive-sense RNA for synthesis of new viral RNA. The aim of our studies was to investigate whether a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
210
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(224 citation statements)
references
References 51 publications
11
210
1
2
Order By: Relevance
“…3A). To determine whether ER stress also augments cytoplasmic dsRNA-mediated induction of IFN-b, we took advantage of HEK293 cells that are unresponsive to exogenous poly(I:C) [32,33], but produce type I IFN following transfection [34]. Similar to the response to TLR4/3 agonists, there is strong synergistic IFN-b induction by transfected dsRNA in cells experiencing ER stress (Fig.…”
Section: Induction Of Type I Ifn In Macrophages Experiencing Er Stressmentioning
confidence: 99%
“…3A). To determine whether ER stress also augments cytoplasmic dsRNA-mediated induction of IFN-b, we took advantage of HEK293 cells that are unresponsive to exogenous poly(I:C) [32,33], but produce type I IFN following transfection [34]. Similar to the response to TLR4/3 agonists, there is strong synergistic IFN-b induction by transfected dsRNA in cells experiencing ER stress (Fig.…”
Section: Induction Of Type I Ifn In Macrophages Experiencing Er Stressmentioning
confidence: 99%
“…They are evolutionarily conserved components and act as sentinels of the innate immune system, sensing a variety of ligands from lipopolysaccharide to flagellin to dsRNA by leucine-rich-repeat motifs (LRRs) in their extracellular domain (West et al 2006;Xu et al 2000;Ishii et al 2007). TLRs are type I transmembrane pattern recognition receptors (PRRs) that detect invading pathogens by binding conserved, microbially derived molecules (pathogen-associated molecular patterns, PAMPs) that are not found in higher eukaryotes, and that signal and induce expression of multiple host defense genes including proinflammatory cytokines and chemokines (Rudd et al 2005). TLRs are the focus of considerable attention as potential regulators and controllers of the immune response through their ability to recognize PAMPs, and are arousing interest as potential targets for the development of new therapies for multiple diseases (Zuany-Amorim et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…TRIF also triggers a signaling cascade that activates NF-B and the transcription of proinflammatory cytokine genes (2). The TLR3 pathway has been implicated in the host responses to respiratory syncytial virus and influenza A virus infections in vitro (14,15) and West Nile virus and murine cytomegalovirus (MCMV) infections in vivo (7,16). However, additional in vivo studies with lymphocytic choriomeningitis virus, reovirus, and MCMV have indicated that antiviral responses are also mediated by pathways independent of TLR3 (17,18).…”
mentioning
confidence: 99%